Proceedings of the First ACM SIGCOMM Workshop on Green Networking 2010
DOI: 10.1145/1851290.1851296
|View full text |Cite
|
Sign up to set email alerts
|

To compress or not to compress - compute vs. IO tradeoffs for mapreduce energy efficiency

Abstract: Compression enables us to shift the computation load from IO to CPU. In modern datacenters where energy efficiency is a growing concern, the benefits of using compression have not been completely exploited. We develop a decision algorithm that helps MapReduce users identify when and where to use compression. For some jobs, using compression gives energy savings of up to 60%. As MapReduce represents a common computation framework for Internet datacenters, we believe our findings will provide signficant impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 4 publications
0
48
0
2
Order By: Relevance
“…It joins others in which the focus is to understand the energy consumption of compression techniques in different scenarios [9], [10]. To the best of our knowledge, this work is the first to study the impact of data deduplication on storage system energy consumption.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…It joins others in which the focus is to understand the energy consumption of compression techniques in different scenarios [9], [10]. To the best of our knowledge, this work is the first to study the impact of data deduplication on storage system energy consumption.…”
Section: Introductionmentioning
confidence: 88%
“…Recently, Chen et al [9] and Kothiyal et al [10] have investigated the trade-off of compressing or not data in the context of MapReduce applications and data centers, respectively. Similar to this work, they concluded that compression is not always the best choice in terms of energy consumption, as it depends on the workload.…”
Section: B Energy Optimized Systemsmentioning
confidence: 99%
“…In the Hadoop compression algorithms, Andre Wenas [2] used compression as follow: GZIP, LZJB and ZLE for data warehouse and his results shows the best performance on ZLE. Yanpei Chen's research [4] tried to select compress or not compress map reduce output file for reducing power consumption. His results shows that it decreases energy consumption more than 50%.Bhavin J. Mathiya [5] use more compression algorithm as follows: DE-FLATE, LZ4, BZIP and GZIP with word-count benchmark both map output and reduce output.…”
Section: Related Workmentioning
confidence: 99%
“…Consequently, this maximizes the number of idle servers that can be deactivated to save energy. Chen et al [5] analyze how MapReduce parameters affect energy efficiency and discuss the computation versus I/O tradeoffs when using data compression in MapReduce clusters in terms of energy efficiency [4]. Chen et al [3] present the Berkeley Energy Efficient MapReduce (BEEMR), an energy efficient MapReduce workload manager motivated by empirical analysis of real-life MapReduce with Interactive Analysis (MIA) traces at Facebook.…”
Section: Related Workmentioning
confidence: 99%
“…As such large-scale deployments become a distinctive characteristic of cloud infrastructures, energyefficient MapReduce is nowadays an essential concern in data-centers. Several studies have explored power saving in Hadoop clusters, through various techniques [2,4].…”
Section: Introductionmentioning
confidence: 99%